Blurring the Boundaries – STEM Education and Education for Sustainable Development - Pitt, James (Design and Technology Education: An International Journal, 2009)
Both the concept of sustainable development and the nature of education for sustainable development (ESD) are highly contested. ESD can be construed as a part of sustainable development policy as governments attempt to bridge the ‘value-action gap’ between what we know we should be doing (e.g. to combat climate change) and what we actually do. Alternatively sustainability can be construed as a ‘frame of mind’; within this paradigm ESD is seen as a way of bringing to the surface underlying values and beliefs through the exploration of contradictions and arguments. STEM (Science, Technology, Engineering and Mathematics) education is equally contested. At one end it is seen as a pre-vocational learning or even training to encourage students to pursue science and maths in particular en route to professional work in engineering and technology. ‘Successful’ STEM is then measured in take-up of certain subjects Post-16 or at tertiary level, or in terms of attitudes towards engineering and technology. Conversely, STEM can be seen as an entitlement to learn in a different way, in which the boundaries between the component subjects of STEM become blurred and learners are encouraged to develop transferable skills and knowledge and the metacognitive skills that enable this transfer to be used creatively. In this paper the author examines how teachers can plan for a creative interaction between ESD within the ‘frame of mind’ approach, and STEM education as a metacognitive entitlement. It argues that current curriculum reforms in England1 offer unprecedented opportunities for design and technology teachers to extend student engagement and learning beyond the prescribed Design and Technology (D&T) curriculum thereby enhancing creativity and critical reflection. Using sustainability contexts for STEM activities might provoke critical discourse within schools and their wider communities, thereby creating new opportunities for ESD.